Tasawuf Sebuah Pendekatan dalam Studi Agama di Indonesia - Najib, Muhammad Ainun; Fata, Ahmad Khoirul; Kango, Andries (Universitas Islam Negeri Imam Bonjol Padang, 2024)
The Sufistic approach in the study of religion is a method that seeks to explore the mystical and esoteric dimensions within various religious traditions, including Islam. This article highlights the use of the Sufistic approach by scholars, both within and outside the Islamic tradition, to understand the phenomenon of Sufism and mystical practices in Muslim communities. This study shows that the Sufistic approach is not only relevant for understanding individual morality and spirituality but also provides a broader perspective on interfaith dialogue and pluralism. Various methods such as phenomenology, historical, and even interreligious approaches are employed in Sufistic studies. Thus, this approach offers a deeper understanding of subjective and symbolic spiritual experiences. However, the study also emphasizes that understanding Sufism requires mastery of complex Sufistic terminology and concepts. This article concludes that, amidst the challenges of modernity and extremism, the Sufistic approach in religious studies remains relevant as an effort to enrich the understanding of religiosity and tolerance among religious communities.